PENGARUH SENAM TERA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI PUSKESMAS BANDAR KHALIPAH - Pandamutu M.T. Samosir; Sridama Yanti Harahap (Universitas Murni Teguh, 2026)
Aging is a process experienced by all people which is characterized by gradual and inevitable physical, social and mental deterioration. One of the diseases that is often experienced by the elderly is hypertension. Tera gymnastics is one of the non-pharmacological therapies that can be used as a therapy for health that can be used to lower blood pressure. The objective of this study is t find out whether there is an effect of tera gymnastics on lowering blood pressure in hypertensive elderly people at the Bandar Khalipah Health Center. The research method used a quantitative research form with a Quasi Experimental research design with a One group Pretest-posttest Design. The data collection technique was purposive sampling with a sample of 30 respondents divided into a control group and an intervention group for comparison. The result showed that before being given the Tera gymnastics intervention, 14 respondents experienced stage 1 hypertension, 14 people with pre-hypertension and 2 people with stage 2 hypertension. After being given tera exercises in the intervention group, the blood pressure experienced by the respondents changed which became Normal for 8 people, pre-hypertension for 14 people and hypertensive stage 1 for 8 people. And after the test was carried out using the parametric paired sample t test, a p value = 0.000. which means that there is an effect of giving tera gymnastics on reducing blood pressure in the elderly at the Bandar Khalipah Health Center. It is concluded that There is a significant effect between the administration of Tera exercises on the reduction of blood pressure in the elderly with hypertension at the Bandar Khalipah Health Center.